MENGHITUNG PERCEPATAN GRAVITASI BANDUL DAN GERAK PARABOLA - Hernelis R (Komunikasi Fisika Indonesia, 2014)
Experiment to calculate gravitational accceleration has been done using physical pendulum and parabolicmotion principles. One pendulum mass was used namely 0.4 kg .Gravitational acceleration for mass isg =29.295 m/s 2 . These results are close enough to the literature 9.81 m / s . Relative error of this gravitydetermination for each pendulum are 5.3 % .